A Case With Reversible Neurotoxicity After 2 Years of Dementia Secondary to Maintenance Lithium Treatment. Issue 2 (March 2015) - SORIANO-BARCELÓ, JUAN; ALONSO, MARÍA TAJES; TRABA, MARÍA BEGOÑA PORTELA; VILAR, ALBERTE ARAÚXO; KAHN, DAVID A.
<x xml:space="preserve">Abstract</x> Chronic neurotoxicity caused by lithium salts can be reversible or irreversible and may appear after years of treatment, even at serum levels considered within the usual therapeutic range. The authors present the case of a patient with bipolar disorder who developed dementia at the age of 54 after being treated with lithium carbonate at therapeutic levels for 4 years. Nevertheless, lithium treatment was continued. At age 56, the patient presented with an acute encephalopathy caused by toxic lithium levels, which resolved only after lithium carbonate was discontinued. Full recovery from the dementia, which had started 2 years earlier, occurred only after cessation of lithium. The authors conclude that when patients treated with lithium develop subacute cognitive impairment, the possibility of lithium toxicity should be considered, even if the serum levels are considered within the therapeutic range. A long duration of neurotoxicity associated with lithium treatment does not necessarily indicate an irreversible prognosis. (Journal of Psychiatric Practice 2015;21:154–159)